PENERAPAN PERMAINAN CONGKLAK/DAKON UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PADA SISWA KELAS 4 - Nada, Qolbiyah Azkan; Amelasasih, Prianggi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to examine the effectiveness of using the traditional congklak game to improve students' arithmetic skills, particularly multiplication, while incorporating positive reinforcement as a motivational tool. Many elementary school students struggle with understanding abstract mathematical concepts, especially multiplication and division. To address this issue, a series of interventions using the congklak game were conducted. The methodology involved four sessions with a fourth-grade student from MI Al-Hidayah Banjarsari. A pre-test assessed the student"™s initial multiplication ability, followed by interventions using congklak, and concluding with a post-test to measure improvement. Throughout the sessions, positive reinforcement"”such as praise and rewards"”was given to maintain the student"™s motivation and focus. The results showed significant progress in the student's ability to perform multiplication, as evidenced by a quicker of problems in the post-test compared to the pre-test. The use of positive reinforcement was effective in maintaining the student"™s motivation during the learning process. In conclusion, the congklak game, combined with positive reinforcement, proved to be an engaging and interactive method for enhancing multiplication skills and could serve as a creative teaching strategy in mathematics education.